Vasospastic Angina and its Relationship with the Coronary Microcirculation - Cenko, Edina; Bergami, Maria; Varotti, Elisa; Bugiardini, Raffaele (Current Pharmaceutical Design, 2018)
Vasospastic angina is an important cause of chest pain due to coronary artery vasospasm that is related to poor quality of life and can lead to myocardial infarction, arrhythmias and death. Since its first description as “Prinzmetal or variant angina” which was believed to be a focal spam that occurred in non-obstructed epicardial coronary arteries, physician and researchers were gradually confronted with the clinical reality and came to the conclusion that the coronary artery vasospasm was considerably more polymorphic than initially described. Although mechanism leading to vasospastic angina is not completely understood, nowadays the medical community acknowledges that it exhibits a large variability in clinical practice ranging from focal to diffuse epicardial vasospasm. Main proposed mechanisms are impairment of parasympathetic activity, coronary vascular and microvascular dysfunction due to blunted response to nitric oxide endothelium-dependent coronary vasodilatation, increased release of vasoconstricts, and oxidative stress.
Keywords: epicardial vasospasm